The effect of food insecurity on health status of adolescents in Ethiopia: longitudinal study - Mulusew G. Jebena; David Lindstrom; Carl Lachat; Tefera Belachew; Patrick Kolsteren (BMC, 2017)
Abstract Background The effect of food insecurity on health and wellbeing of a population has been the subject of much research. Yet, limited research has investigated its effect on adolescents' health and wellbeing in Ethiopia. Method We used data from the Jimma Longitudinal Family Survey of Youth which began tracking a cohort of adolescents in 2005 to examine the social, behavioral and economic determinants of their health and well-being. A total of 1,919 sample were included in the main analyses. All youths provided data related to their food insecurity experiences and their health status. A mixed effect logistic regression using random intercept and trend model was used to examine the relationship between food insecurity and their health status. Fixed effects estimates were also computed to check the parsimoniousness of the random intercept and trend model. Results The results indicated that the mean (±SD) age of adolescents was 18.6(±1.4). Nine hundred twenty three (48.1%) of them were female. The magnitude of self-rated health status was relatively unstable ranging from 18.9%, 34.7% to 37.3% in each round. Similarly, 20.4%, 48.4% and 20.6% of adolescents were food insecure during each consecutive round of the survey respectively. Exposure to food insecurity is strongly associated with self-rated health status (β = 0.28, P < 0.001) and poor self-rated health was also more pronounced for some time (β =2.11, P < 0.001) and decline after a turning point (β = −0.38, P < 0.001). Conclusions These findings imply that any social, nutrition and public health interventions designed to improve adolescent health should consider underlying social determinants of health such as food insecurity.